Evaluasi Kebijakan Publik dalam Penanggulangan Kebakaran Industri: Studi Kasus Smelter Morowali - Ridwan, M.; Frinaldi, Aldri; Rembrandt; Lanin, Dasman (Innovative: Journal Of Social Science Research, 2024)
The nickel smelting industry in Morowali, Central Sulawesi, contributes significantly to the economy but faces substantial challenges in occupational safety. Recurrent fires in these smelters highlight deficiencies in the implementation of occupational health and safety (OHS) policies, as well as their impacts on workers and the surrounding environment. This study aims to evaluate the effectiveness of public policies in mitigating fire risks in smelter industries, focusing on identifying root causes, policy implementation, and the role of oversight. The study adopts a qualitative approach with descriptive methods, analyzing regulatory documents, fire incident reports, and media articles. The analysis reveals that the primary causes of fires include procedural negligence, inadequate safety infrastructure, and weak OHS implementation. Insufficient government oversight and inadequate employee training further exacerbate the issue. Key findings indicate that existing regulations are not fully effective due to inconsistent implementation in practice. The study recommends strengthening oversight, enforcing strict penalties, and enhancing safety training for workers. In conclusion, with integrated improvement measures, fire risks can be minimized, creating a safer and more sustainable working environment.